Crisis as Catalyst: The Moral Origins of Collaborative Governance in Tourism Village - Sutrisno, Andang Nugerahatara; Damanik, Janianton; Widaningrum, Ambar (Universitas Teuku Umar, 2025)
This study aims to explore how culturally rooted moral crises can trigger the emergence of collaborative governance in rural tourism development. While collaborative governance has become a normative approach in sustainable tourism, existing literature rarely examines how emotionally charged incidents catalyze stakeholder mobilization. This research investigates the case of Kaligono Village, Indonesia, where the misuse of a sacred waterfall provoked widespread moral outrage and initiated community-led governance transformation. Using a single embedded case study design, data were collected through 19 in-depth interviews, participant observation, and document analysis over six months. The findings show that the moral crisis activated inclusive village deliberations, reasserted collective values, and fostered grassroots leadership. These dynamics evolved into a formalized collaborative governance regime featuring dual Pokdarwis (tourism groups), village regulations, enforceable SOPs, and multi-level partnerships. The study introduces the concept of crisis-led collaborative genesis, emphasizing the role of moral rupture in aligning stakeholders through shared cultural identity and emotional resonance. It concludes that in contexts of strong cultural cohesion, a crisis can serve as a disruption and a foundational moment for participatory and resilient governance. These insights offer practical implications for tourism planning in culturally embedded rural settings.